Liquid state diodes using polymer semiconductors - Sönmez, Bedri Gürkan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
In this thesis a liquid state polymer diode is fabricated and characterized. First, lateral electrode structures are formed where highly doped p-type Si is used as anode, aluminum is used as cathode and SiO2 is used as seperation and insulation layer. 40 nm SiO2 coated Si wafers are purchased and an aluminum layer with thickness of 200 nm is deposited on top of them. By patterning Al layer and dicing the wafer, samples are obtained which carry a Si/SiO2/Al lateral electrode structure at their sides. After forming electrode structure, polymer solution is prepared. Poly(3-hexylthiophene-2,5- diyl) is used as polymer and dichlorobenzene is used as solvent. Polymer solution is poured onto the Si/SiO2/Al interface and by applying voltage between electrodes lateral liquid state polymer diode is formed. Fabricated diodes are tested and characterized. Effects of time and solution concentration on performance characteristics are examined. In measurements, 315 mA/cm2 current density is achieved for 6 mg/ml solution at 7 V which is at least six fold better than the current density of its solid counterpart for the same situation. Also back and forth voltage sweep measurements are applied to investigate hysteresis effect. It is seen that zero current is obtained at −0.7 V when the sweep goes from −10 V to +10 V and for reverse sweep zero current is obtained at +1.4 V.
Keywords: Diodes, Semiconductor.